Тихий Дон: [роман] (Михаил Шолохов) - Шолохов Михаил Александрович (Русская классика, 2009)
Экземпляры: РБ (20211029) / Инвентарный номер: 62322 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ш 79 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6